Evaluating technology breaks on cell phone use in a college classroom - Redner, Ryan; Hurtado-Parrado, Camilo; Cifuentes, Julian; Shawler, Lesley A.; Jacobs, Eric A. (Frontiers in Education, 2024)
Cell phones in the college classroom can be used to increase interaction between students and the professor; They can also distract from academic tasks and decrease academic performance. To decrease task-switching in the classroom, researchers have suggested the use of "technology breaks" (TB), in which students are provided periodic breaks to use cell phones throughout class. The purpose of the present study was to evaluate the use of technology breaks in a college classroom (N = 21). Cell phone use was evaluated over 22 class periods. Observers recorded how many students were using cell phones every 10 s. Three experiment conditions were alternated with yoked controls in a multi-element design: (A) 1 min technology breaks, (B) 2 min technology break, and (C) 4 min technology break. The control condition (question breaks, [QB]) provided breaks for students to ask the professor questions regarding class materials. No penalties or punishers were delivered for cell phone use under any conditions. The average rate of cellphone use in QB was 0.53 responses per min (range = 0.06-1.02), while the average rate for TB was 0.35 responses per min (range = 0.20-0.74). Overall, the study found that technology breaks were a promising way to utilize reinforcement-based strategies to reduce classroom cell phone use, though variability in the data weakened conclusions regarding the utility of technology breaks.